Correction to: Antecedents of Business Tourist Loyalty: The Moderating Role of Familiarity and Emotional and Cognitive Experiences (Review of Managerial Science, 2025 10.1007/S11846-025-00852-7) - Marinao-Artigas, E (Springer Science and Business Media Deutschland GmbH, 2025)
In the original version of this article, the author’s name Karla Barajas-Portas was incorrectly written as Karla Barjas-Portas. The affiliation details for the author Karla Barajas-Portas were incorrectly given as Facultad de Economia y Negocios, Universidad Anáhuac, Campus Norte, Lomas Anáhuac, Ciudad de Mexico, Mexico but should have been ‘Universidad Anáhuac, Ciudad de México, México . The original article has been corrected. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2025.